2014
DOI: 10.1016/j.bpj.2014.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Base-Modified DNA Are Not Strictly Determined by Base Stacking or Electrostatic Interactions

Abstract: This work probes the mystery of what balance of forces creates the extraordinary mechanical stiffness of DNA to bending and twisting. Here we explore the relationship between base stacking, functional group occupancy of the DNA minor and major grooves, and DNA mechanical properties. We study double-helical DNA molecules substituting either inosine for guanosine or 2,6-diaminopurine for adenine. These DNA variants, respectively, remove or add an amino group from the DNA minor groove, with corresponding changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 58 publications
7
30
0
Order By: Relevance
“…This result is consistent with what has been reported previously for experiments using AFM and optical tweezing (14,19). Similarly, previously reported MT experiments measuring DNA under supercoiling found that DAP substitution increased the size of plectonemic writhes, a finding that is consistent with DAP-DNA being harder to bend (6).…”
Section: Dap Substitution Increases Melting Temperature But Preservessupporting
confidence: 92%
See 4 more Smart Citations
“…This result is consistent with what has been reported previously for experiments using AFM and optical tweezing (14,19). Similarly, previously reported MT experiments measuring DNA under supercoiling found that DAP substitution increased the size of plectonemic writhes, a finding that is consistent with DAP-DNA being harder to bend (6).…”
Section: Dap Substitution Increases Melting Temperature But Preservessupporting
confidence: 92%
“…To further investigate the effect of DAP substitution upon DNA conformational stability in the low-tension (entropic) and high-tension (overstretching) regimes, we performed a series of atomic force microscopy (AFM) imaging, magnetic tweezer (MT)-based stretching, circular dichroism (CD) spectroscopy, and thermal melting experiments on equivalent WT and DAP-substituted DNA sequences. The AFM and MT experiments confirm the findings of Virstedt et al and Peters et al that under low tension, DAP-DNA is flexurally stiffer (14,19). Interestingly, the AFM and MT assays yielded conflicting measurements of molecular contour length.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations